The Prevalence of Some Intestinal Parasites in Stray Dogs From Tetova, Fyr Macedonia - Abdilazis Llokmani; Dhimitër Rapti (European Scientific Journal, ESJ, 2017)
Stray dogs are a reservoir of intestinal parasites and a source of infection for pet dog owners. Some parasites, including hookworms and roundworms, are zoonotic parasites. This means they can easily be transmitted from pets to humans. The present study aims to determine the prevalence of intestinal parasitic infections in stray dogs located in Tetova, FYR Macedonia region between February to April 2017. A total of 60 samples were examined by centrifugation-flotation methods. The overall prevalence of gastrointestinal parasites were 0,40%, 0,13%, 0,08%, and 0,01% for Ancylostoma spp., Trichuris vulpis , Toxocara canis and Coccidia respectively. Stray dogs are associated with a high risk of infection. Also, the periodic laboratory tests can confirm this. The information received from this present study may be useful in the designing of control programs. It was also used in educating the dogs’ owners about public health issues of dog keeping, hence reducing the risks associated with zoonotic infections.